Pemilahan dan Pendeteksi Kualitas Telur Ayam Terbaik Berbasis Mikrokontroler Menggunakan Arduino Nano - Muhammad Irfan; Poning Sih; Sundari Retno Andani; Indra Gunawan; Irawan Irawan (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
Eggs have become the main consumption for the community such a neighborhood and marketplace. Therefore the development of chicken farming is getting bigger. Especially in the chicken egg-producing sector. There are still many chicken egg breeders who still use traditional methods such as sorting by binoculars and smell is not enough to know the good quality of eggs properly. Here the author designs a tool that can overcome these problems. The Egg Sorter and detector using a nano microcontroller and photodiode sensor is a control system that work by sorting the good and bad quality of chicken eggs by put the eggs on the conveyor and scanning it using photodiode sensor that will detected it which eggs are good or not. And after that the data will be sent to the microcontroller to drive the servo motor to set aside poor quality eggs by pushing eggs out of the path while eggs with good quality will passing by and go to container that containing eggs with a good quality one. The purpose of this Egg sorting is to minimize the existence of defects in eggs and facilitate the process of sorting eggs before the eggs are distributed to the market and also before consumption by consumers. The results of this study are to help poultry ease their work in checking the quality of eggs so as to provide a sense of security and ease in monitoring poultry production.